PENINGKATAN MOTIVASI BELAJAR MATEMATIKA DENGAN MELAKUKAN MANAJEMEN KELAS PADA SISWA KELAS IV SDN 002 SUNGAI PINANG SAMARINDA TAHUN PELAJARAN 2016/2017 - Euis Kusuma Rini (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
Classroom Management is the way the teacher handles the classroom by means of arrangements that include ventilation, lighting, comfort and placement of learners in the classroom. This research is a classroom action research, the purpose of this research is to improve the motivation of learning and student learning outcomes of grade IV-B which amounted to 30 people at SDN 002 Pelita Sungai Pinang Samarinda. This study was conducted in four cycles consisting of planning, implementation, observation and reflection. Each meeting of the researcher conducted a direct observation and recorded it.At the end of each cycle, there will be a written test. Preliminary data is taken from Pre Cycles performed before cycle I begins. While the final data obtained at the end of each cycle after the test. The collected data was analyzed quantitatively using the frequency table and mean score and determined the level of learning result category. which became the benchmark of the success of this study if 75% of students obtained a KKM score of 65, from the test results. Then the class is considered completeKeywords: Motivation Learning Mathematics and Classroom Management